2007
DOI: 10.1007/s10764-007-9184-y
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Assessment of Macaque Tourist Sites in Padangtegal, Bali, Indonesia, and the Upper Rock Nature Reserve, Gibraltar

Abstract: Human tourists share space with, touch, feed, and otherwise interact with Macaca at multiple locations. Across Asia and stretching to Gibraltar and Northern Africa, macaques form a substantial tourist attraction as their ranges become increasingly coincident with human use zones. Residing in or as tourist attractions, macaques frequently generate economic benefits to local humans and compete with them for habitat and specific resources. In addition, health conflicts may emerge from increased overlap and intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 14 publications
2
44
0
1
Order By: Relevance
“…At VWM, park staff practices of encouraging tourists to hand-feed monkeys and allowing tourists to pose for pictures with monkeys on the platform have not been seen since 2005, but it is still the case that tourists often arrive with food and the apparent intent of feeding monkeys, and tourists disregard the staff's admonitions against doing so. Signs were posted throughout VWM stating that monkeys should not be fed, but as was true at the sites studied by Fuentes et al (2007), we found that tourists ignored signage.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…At VWM, park staff practices of encouraging tourists to hand-feed monkeys and allowing tourists to pose for pictures with monkeys on the platform have not been seen since 2005, but it is still the case that tourists often arrive with food and the apparent intent of feeding monkeys, and tourists disregard the staff's admonitions against doing so. Signs were posted throughout VWM stating that monkeys should not be fed, but as was true at the sites studied by Fuentes et al (2007), we found that tourists ignored signage.…”
Section: Resultsmentioning
confidence: 72%
“…However, without continued careful management of tourist-monkey interactions, VWM could become more similar to Mt. Emei or other sites where higher rates of monkey-human aggression have been reported (Zhao and Deng 1992;Fuentes and Gamerl, 2005;Zhao 2005;Sabbatini et al 2006;Fuentes et al 2007). It is also possible that tourism poses a stressor to VWM monkeys, thereby undermining the conservation and research goals established for the site (Berman and Li 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our observations showed that the macaques were relatively well adapted to the presence of visitors, more so than other prey species in the valley. The macaques successfully occupy disturbed habitats including tourism areas [Eudey, 2008;Peterson and Riley, 2013] and can cope with the tourists' presence and activities [Biquand and Gautier, 1994;Fuentes et al, 2007]. The macaques' ability to persist in tourist-dominated areas sympatrically with Komodo dragons [Fuentes et al, 2007] increases their predation risk due to their relative abundance compared to other prey species (i.e., water buffalo and feral pigs), which actively avoid tourist-occupied areas.…”
Section: Discussionmentioning
confidence: 99%
“…Relationship between tourism and wildlife could be parasitic, coexistent or symbiotic (Jacobson & Lopez 1994). Even for the same species, tourism could represent a commensal relationship, or a wide source of disturbances, as the case of macaque in Asia (Fuentes et al 2007). An apparent benefit in population abundance possibly hide other severe disturbances, such as changes in diet, social and foraging patterns, not assessed in this study.…”
mentioning
confidence: 99%